2008
DOI: 10.1029/2007jd009018
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between ion balance and the chemical compounds of salt inclusions found in the Greenland Ice Core Project and Dome Fuji ice cores

Abstract: ). The method is demonstrated for the Holocene and last glacial maximum regions of the Dome Fuji and GRIP ice cores. The dominant compounds depend only on the ion balance and the sequence of chemical reactions. In priority order, the principle salts are calcium sulfate, other sulfates, nitrate, chloride, and carbonate. The chemical abundances deduced by this method agree well with the results of Raman spectroscopy on individual salt inclusions. The abundances in the ice cores are shown to reflect differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 40 publications
11
75
0
Order By: Relevance
“…Previous studies suggest that the formation of CaSO 4 Á2H 2 O by neutralized reaction of terrestrial dust (i.e. Ca 2+ ) with non-sea-salt sulfuric acid is dominant especially in the glacial maxima (Rö thlisberger and others, 2003;Ohno and others, 2006;Iizuka and others, 2008b). On the other hand, gypsum (CaSO 4 Á2H 2 O) was found in the rock wall of a dry valley in the Sør Rondane Mountains, Antarctica (Matsuoka, 1995;Matsuoka and others, 1996).…”
Section: Chemical Forms Of the Microparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggest that the formation of CaSO 4 Á2H 2 O by neutralized reaction of terrestrial dust (i.e. Ca 2+ ) with non-sea-salt sulfuric acid is dominant especially in the glacial maxima (Rö thlisberger and others, 2003;Ohno and others, 2006;Iizuka and others, 2008b). On the other hand, gypsum (CaSO 4 Á2H 2 O) was found in the rock wall of a dry valley in the Sør Rondane Mountains, Antarctica (Matsuoka, 1995;Matsuoka and others, 1996).…”
Section: Chemical Forms Of the Microparticlesmentioning
confidence: 99%
“…In fact, for instance, we found Mg(CH 3 SO 3 ) 2 Á12H 2 O (Sakurai and others, 2010b) and the spectrum of nitrate salt with an unknown cation in LGM ice. Previous studies have shown that chloride salt may have existed in the LGM (Rö thlisberger and others, 2003;Iizuka and others, 2008b). Therefore, Equations (1) and (2) are useful tools for estimating the chemical forms of microparticles based on ion concentrations in the ice.…”
Section: Chemical Forms Of the Microparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both solutions were used as the Ca ++ concentration could not be accurately measured until after the completion of each test, which showed a range of Ca ++ concentrations between 5 and 50 ppm. The ionic compound CaSO 4 was chosen as the dopant as it is found to exist in and be deposited on ice sheets and glaciers (Legrand and Mayewski, 1997;Obbard and Baker, 2007;Iizuka and others, 2008). Furthermore, it was shown by Fujita and others (2014) that SO 4 −− was one of the least likely to contribute to firn densification and ice deformation, showing very poor correlations with densification, thereby also making CaSO 4 a good candidate for studying the effects of Ca ++ .…”
Section: Experimental Performed In the Dartmouth Ice Research Laboratmentioning
confidence: 99%
“…(Watanabe and others, 2003). The six ions are the most common species in the DF core (Iizuka and others, 2008). Note that the K + concentration in the DF ice core is so small (Watanabe and others, 2003) that it is occasionally absent from the ion chromatogram, and so was left out of the PCA.…”
mentioning
confidence: 99%